The responsibility of clinical pharmacists for the safety of medication use in hospitalized children: A Middle Eastern experience - Khatereh Jafarian; Zahra Allameh; Mehrdad Memarzadeh; Ali Saffaei; Payam Peymani; Ali Mohammad Sabzghabaee (Wolters Kluwer Medknow Publications, 2019)
Objective: We aimed to detect and report the frequency of occurrence of drug-related problems (DRPs) in a Middle Eastern University Children's Hospital (Isfahan, Iran) and classify them in terms of their nature and cause to clarify the responsibility of clinical pharmacists for the safe utilization of medications in hospitalized children. Methods: In this cross-sectional study which was carried out in Imam Hossein Children's University Hospital affiliated with Isfahan University of Medical Sciences (Isfahan, Iran) from September 2017 to May 2018, DRPs during the hospitalization of pediatric patients in three medical wards, the pediatric intensive care unit, and two neonatal intensive care units were detected and identified concurrently with the treatment process using Pharmaceutical Care Network of Europe data gathering form for DRPs v. 8.01. All cases were verified and validated in a professional focus group before documentation. Findings: We detected 427 DRPs in 201 out of 250 randomly included hospitalized children in which 86% of them were directly reported by the hospital's clinical pharmacist. The highest frequency of DRPs (47.3%) was observed in the age range of 1 month-2 years. Safety of treatment was the most frequently reported as the nature of the problem (43.5%), followed by effectiveness issues (36.8%). The most frequent cause of DRPs was dose selection issues (34.2%), followed by drug-type selection (25.5%), and unavailability of appropriate dosage forms (13.6%). Ninety-eight interventions were proposed by the clinical pharmacist, in which 59.2% of them were accepted. Conclusion: This study confirms the necessity for the active role of clinical pharmacists before, during, and after drug therapy in hospitalized pediatric patients for the safety and proper utilization of drugs in this vulnerable population.